2022
DOI: 10.1177/17474930221088400
|View full text |Cite
|
Sign up to set email alerts
|

A Phase III, prospective, double-blind, randomized, placebo-controlled trial of thrombolysis in imaging-eligible, late-window patients to assess the efficacy and safety of tenecteplase (TIMELESS): Rationale and design

Abstract: Rationale: While thrombolysis is standard of care for patients with acute ischemic stroke (AIS) within 4.5 hours of symptom onset, the benefit of tenecteplase beyond this time window is less certain. Aim: The TIMELESS trial (NCT03785678) aims to determine if treatment with tenecteplase increases the proportion of good clinical outcomes among patients with stroke due to a large vessel occlusion who present beyond 4.5 hours after symptom onset. Sample size estimates: A total of 456 patients will provide ≥90% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Current studies are exploring whether IVT is safe and effective beyond 4.5 hours. 28 The second most common reason that stroke patients did not received IVT was that patients were taking anticoagulants. Concordant with the 2018 American Heart Association guidelines that give a Class III (potentially harmful) recommendation against empirically treating patients on direct oral anticoagulants (DOACs) with IVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies are exploring whether IVT is safe and effective beyond 4.5 hours. 28 The second most common reason that stroke patients did not received IVT was that patients were taking anticoagulants. Concordant with the 2018 American Heart Association guidelines that give a Class III (potentially harmful) recommendation against empirically treating patients on direct oral anticoagulants (DOACs) with IVT.…”
Section: Discussionmentioning
confidence: 99%
“…Among 414 patients with wake‐up strokes or who were between 4.5 and 9 hours from stroke onset, patients who received IVT had better functional outcomes at 3 months, though greater rates of symptomatic intracerebral hemorrhage. Current studies are exploring whether IVT is safe and effective beyond 4.5 hours 28 …”
Section: Discussionmentioning
confidence: 99%
“…A proof-of-concept, prospective, open-label, nonrandomized phase II study demonstrated the feasibility of treating patients with AIS for up to 24 h with TNK [28]. TIMELESS-A Phase III, double-blind, randomized, placebo-controlled trial of TNK in patients with AIS and evidence of salvageable tissue on baseline CT perfusion or MR perfusion within 4.5–24 h after onset with LVO is ongoing [29]. Similarly, other ongoing extended window trials, including ETERNAL-LVO (NCT04454788), ROSE-TNK (NCT04752631), CHABLIS-TII Trial (NCT04516993) and TRACE III (NCT05141305), are randomizing patients with LVO with salvageable penumbra on CT or MR-based imaging, up to 24 h from symptom onset to TNK vs. standard of care.…”
Section: Current Evidence For Tenecteplase In Ischemic Strokementioning
confidence: 99%
“…Similarly, the recently completed TIMELESS study (Tenecteplase in Stroke Patients Between 4.5 and 24 Hours) used multimodal imaging to select patients for intravenous tenecteplase at both primary and comprehensive stroke centers in the late time window. 11 The low proportion of patients enrolled in TIMELESS at primary stroke centers (5% of the study population) highlights the need to increase the number of primary stroke centers that are familiar with multimodal imaging and that have the infrastructure to conduct clinical stroke trials. Multimodal imaging at primary stroke centers may also benefit trials of brain cytoprotective therapy.…”
Section: Research Priorities In Imaging and Systems Of Carementioning
confidence: 99%